PENGARUH METODE PICTORIAL RIDDLE BERBASIS AUGMENTED REALITY (AR) TERHADAP BERFIKIR KREATIF SISWA KELAS XI SMA NEGERI 1 ANGKOLA TIMUR - Kasmawati, Kasmawati; Nasution, Eni Sumanti; Siregar, Meilita (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
The aim of this research is to determine the significant influence of student creativity on the subject of static fluids after implementing the AR-based pictorial riddle learning model in class XI of SMA Negeri 1 Angkola Timur. This research is a Quasi Experimental Research. The instruments in this research were essay test instruments and student observation sheets. The population is 270 class XI students of SMAN Negeri 1 East Angkola and the sample here uses a cluster random sampling technique with an experimental class of class Based on the research data obtained and the results of the statistical tests that have been carried out, it can be concluded that there is a significant difference between the average score and the results of the t-test analysis of two independent samples. The average post-test score for the experimental class was 77.30, more than higher than the post-test average score in the control class of 69.13. The statistical test results show that tcount 2.72 > ttable 1.717, for a significance level of 95% and α = 0.05 so that Ha is accepted and H0 is rejected. So it can be concluded that through the application of the pictorial riddle learning model, it can improve students' ability to think creatively in Class XI of SMA Negeri 1 Angkola Timur..